P-EYE THE ANDROID APPLICATION TO TRACK STUDENTS ACADEMIC PERFORMANCE - MOHAMMED BAWAZIR (International Journal of Computer, Network Security and Information System, 2022)
This paper describes the design and implementation of a software application, the application been designed for smart mobile devices with an android operating system, the app is created to be considered as a tool for parents to help them on tracking their children’s performance in elementary school. The implemented application entitled parents to know the most important details about their children’s academic status, by providing for them a set of features in the app they can use, and also to be connected with the school’s administration.